Gagasan Inovasi Ilmu Pendidikan Islam Perspektif Buya Hamka - Nabila Syafira Antonia; Nur Berliana Islami; Naura Bunga Zaiyan; Moh. Faizin (Moral : Jurnal kajian Pendidikan Islam, 2025)
In this study, we will discuss the concept of Islamic education from Buya Hamka's perspective. Buya Hamka was an Indonesian Muslim cleric and scholar with a profound perspective on the relationship between knowledge, faith, and morality. The purpose of this study is to analyze aspects of Islamic education according to Buya Hamka and their relevance to the modern education system. This research was conducted using a qualitative descriptive approach, drawing on relevant academic literature such as journals, books, and articles. This research concludes that Buya Hamka views Islamic education as an effort to shape a holistic human being, balancing spiritual, intellectual, moral, and social aspects. Hamka emphasized that education is not only intended to cultivate the intellect but also to purify the heart and develop noble character. According to Hamka, Islamic education must be grounded in monotheism, direct educators as role models of morality, and integrate religious and intellectual knowledge for the benefit of the community. Buya Hamka's perspective is sufficient to address the challenges of modern education, which tends to focus on academic values ​​without considering the instilling of moral and spiritual values.